Perceived parental involvement and study attitude of selected high school students - Aninao, Deniese Aileen B.; Chua, Consuelo Trio (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
This study determined the level of parental involvement that high school students receive from their parents. It also described the study attitudes of high school students and looked into the relationship between parental involvement and the study attitudes of the students. Furthermore, the study determined the influence of gender to parental involvement and study attitudes. Seventy one (71) third year high school students, 40 males and 31 females, participated in the study. The students were aged 13 to 17 years old and were enrolled in a public school in Metro Manila. Students in this school come from diverse family and socio-economic backgrounds. A three part self-administered survey was utilized to gather the demographic profile of the students as well as to measure parental involvement and the study attitudes of the students. Results showed that most of the parents are moderately involved in their children's education. The study also found a direct relationship between parental involvement and the study attitudes of the students. In addition, the results indicated that gender does not have an influence on parental involvement and study attitudes of high school students. The study provided recommendations for the development and implementation of school activities that would increase the involvement of parents in their children's education. Recommendations for future researchers were also provided.
Thesis Classification: F (Available for Public)
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: High school students -- Philippines; Education, Secondary -- Parent participation -- Philippines